Sosialisasi Profil Pelajar Pancasila Dan Pembuatan Perangkat Pembelajaran Berbasis Profil Pelajar Pancasila Bagi Guru-Guru PAUD - Radja, Petrus Logo; Hawali , Rebeka F.; Tamelab, Maryance F.; Saefatu, Irony D.; Jaga, Maria Regina; Tunbonat, Winda (Devotion: Jurnal Pengabdian Masyarakat, 2022)
This community service activity is motivated by many PAUD teachers who still do not understand the importance of the Pancasila Student Profile and the implementation of the Pancasila Student Profile in PAUD Learning. The aims are 1) to provide knowledge or education to teachers regarding the Pancasila Student Profile in PAUD Learning; 2) to provide training in making learning tools based on Pancasila student profiles. The method used in this service is the lecture method in the form of socializing the Pancasila Student Profile and practice in the form of assisting in the preparation of teaching tools based on the Pancasila Student Profile. The results of the Community service activity, include the following components: 1) The success of the target number of participants in the socialization activity exceeds 50%; 2) The achievement of the objectives of the social, in generalization activities; 3) Achievement of the planned activity targets. In planning the total number of activity participants are 60 participants who are divided into 2 activity locations. In its implementation, the activity was attended by 50 participants so that the target of the activity participants reached 83.3%